Efficacy of cranial electrotherapy stimulation in patients with burning mouth syndrome: a randomized, controlled, double-blind pilot study - Palmer, Annalena; Hamann, Till; Liese, Jan; Müller, Britta; Kropp, Peter; Jürgens, Tim P.; Rimmele, Florian (Frontiers in Neurology, 2024)
Background The Burning mouth syndrome (BMS) is a chronic pain syndrome characterized by a burning sensation in the oral mucous membranes. The etiology and pathophysiology of BMS is largely unexplained. To date, there is no evidence-based treatment strategy for BMS. Cranial electrical stimulation (CES) represents a non-invasive treatment option with a low side effect profile that is approved for the treatment of pain, depression, anxiety disorder and insomnia. It has shown efficacy in studies for chronic pain such as fibromyalgia and neuropathic pain after spinal cord injury. This study aimed to investigate the therapeutic effectiveness of CES in combination with local transcutaneous electrical nerve stimulation (TENS) as an adjunct therapy in patients with BMS compared to sham stimulation. Methods This randomized, double-blind, sham-controlled pilot study enrolled 22 patients, aged 18 years and over, with the diagnosis of BMS meeting the ICHD-3 criteria from August 2020 to June 2021. The study duration was 4 weeks (28 days) per participant. After randomization, the active group participants (n = 11) received a 100 μA CES treatment for 60 min a day whereas the devices in the Sham group did not emit electricity. Simple linear regression was used to determine whether the interventions promoted significant differences in pain intensity. Results The linear regression showed that the period of stimulation significantly predicted decrease in the intensity of pain in the active group [β = −0.036; t(26) = −7.219; p < 0.001] as in the sham group [β = −0.026; t(26) = −2.56; p < 0.017]. With the applied cutoff of 30% pain reduction within the stimulation period, both the active and sham groups had 36% responders (n = 4) (Fisher’s exact test, p = 1.00). In both groups (active stimulation and sham group), a significant decrease in the intensity of pain, somatic symptoms and an improvement in sleep quality over the study period was observed. Subjects reported no adverse events during the study. Conclusion Although CES is an easily applicable and safe therapeutic option for chronic facial pain, active stimulation was not superior to sham stimulation. Among other reasons, this could be due to the short double-blinded treatment period, duration of the daily stimulation session or the small sample size.